Isolation Discovery of the Role of Dihydrotestosterone: the Work of Jean D. Wilson - Kresge, Nicole (American Society for Biochemistry and Molecular Biology, 2010)
The Conversion of Testosterone to 5α-Androstan-17β-ol-3-one by Rat Prostate in Vivo and in Vitro (Bruchovsky, N., and Wilson, J. D. (1968) J. Biol. Chem. 243, 2012–2021) The Intranuclear Binding of Testosterone and 5α-Androstan-17β-ol-3-one by Rat Prostate (Bruchovsky, N., and Wilson, J. D. (1968) J. Biol. Chem. 243, 5953–5960)